Peningkatan teknik dasar sepak bola dengan metode pelatihan dan kondisi fisik - Zul Fadli Rambe, Ahmad; Yanuar Kiram , Phil; Arsil, Arsil; Bahtra , Ridho; Ockta, Yovhandra (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2024)
This study aims to investigate the effect of small-sided games and rondo training methods, as well as physical conditions, on the basic technique skills of passing, controlling, and dribbling soccer players. This research mode is a Quasi-Experiment with a factorial research design. The sample consisted of 38 child soccer athletes aged 10-12 years from the Wijaya men's soccer team, with purposive sampling from young soccer players (10-12 years) from the Wijaya men's soccer team in Padang. Skill measurements are performed with bounce board instruments for passing control, dribbling tests, agility tests (Illinois Agility Run Test), and speed tests (30-meter run) to measure physical condition. Data analysis using a two-track ANOVA test with a significance level of α 0.05. The results showed that there was a significant difference in the effect of the Small-Sided Games and Rondo methods on passing control (F = 5.931, p = 0.025 < 0.05) and dribbling (F = 61.588, p = 0.000 < 0.05) soccer players. In addition, there is a difference between high and low physical conditions for passing control and dribbling (α < 0.05). Furthermore, there was a significant interaction between training methods and physical condition on passing control (F = 9.481, p = 0.007 < 0.05) and dribbling (F = 88.817, p = 0.000 < 0.05). This study concluded that small-sided games, rondo training methods, and physical conditions have a significant effect on the basic skills of soccer players.